The Newton‐Kleinman method for the optimal control of stable weakly regular linear systems. Issue 1 (October 2016) - Massoudi, Arash; Reis, Timo
Abstract: We give an algorithm to find the approximate solution of the linear‐quadratic optimal control problem for stable weakly regular linear systems. This algorithm can be understood as a generalization of the Newton‐Kleinman method known from the finite‐dimensional theory. The central characteristic of our approach is the possibility to solve problems with unbounded control and observation operators, which is motivated by partial differential equations with boundary control and observation. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)